Investigation of scale effect of numerical unconfined compression strengths of virtual colluvial–deluvial soil–rock mixture. (July 2015) - Zhang, Shu; Tang, Huiming; Zhan, Hongbin; Lei, Guoping; Cheng, Hao
Abstract: A series of numerical unconfined compression tests for virtual pseudo three-dimensional colluvial–deluvial soil–rock mixture (CDSRM) specimens with different areal block proportions ( BP s), sizes and slenderness ratios were conducted to study the variations of strength, deformability and failure process. Surrogate models of the specimens were generated on the basis of statistical characterization of the mesostructures extracted from the outcrop images of Baishuihe landslide site located in Three Gorges Reservoir Area of China. We find that the strength exhibits reduction for higher BP s and exhibits enhancement for lower BP s when the size increases and become asymptotic eventually. The deformability shows a monotonically increasing linear correlation with the specimen size for most BP scenarios. Simultaneously, the strength and deformability values decrease with the specimen slenderness monotonously. These findings are different from the previous assumption that the geo-mechanical behavior of bimrock is scale-independent. Comparing the observations of this study with the reported scale effect of other geotechnical materials, we conjecture that the scale effect is due to the block size and distribution. Graphical abstract: Highlights: We set a constant block/matrix threshold for colluvial–deluvial soil–rock mixture. Unconfined compression test has been performed to virtual specimens. This bimsoil has a great deal of small blocks and limited large blocks. The universal soil/rock threshold underestimates the block proportion and strength. The strength and deformability are scale dependent.